Release of growth factors from a reinforced collagen GAG matrix supplemented with platelet rich plasma: Influence on cultured human meniscal cells. Issue 2 (7th October 2013) - Howard, Daniel; Shepherd, Jenny H.; Kew, Simon J.; Hernandez, Paula; Ghose, Siddhartha; Wardale, John A.; Rushton, Neil
ABSTRACT Damage to meniscal cartilage has been strongly linked to accelerated articular wear and consequently to osteoarthritis. Damage might be ameliorated by delivery of growth factors from platelet rich plasma (PRP) via a fiber reinforced collagen matrix designed for meniscal repair. PRP composition, release of growth factors, and influence on meniscal cell growth and gene expression were investigated. PRP was prepared using Harvest Smartprep (HS‐PRP), Cascade Fibrinet (CF‐PRP), and a simple centrifuge protocol (DC‐PRP) from four donors each. CF‐PRP had the highest ratio of platelets, with very few other blood cell types. HS‐PRP had the highest total number of platelets but also contained high levels of red and white blood cells. Absorbed to collagen matrices HS‐PRP released the highest levels of TGF‐β1 and PDGF‐AB with DC‐PRP the most IGF‐1. Cumulative release from collagen matrix was 48 ng/cm3 IGF‐1, 96 ng/cm3 TGF‐β1, and 9.6 ng/cm3 PDGF‐AB. Collagen matrix with PRP was able to increase meniscal cell number above peripheral whole blood and up‐regulated gene expression of Aggrecan, Collagen type I (α1), and Elastin (3.3 ± 0.8‐fold, 2.9 ± 0.6‐fold, 4.0 ± 1.4‐fold, respectively). Demonstrating that PRP combined with fiber reinforced collagen matrix could influence meniscal cells and might be of use for treating meniscal defects. © 2013 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 32:273–278, 2014.